Laboratory Evaluation of Engineering and Strength Properties for Semi Rigid Mixtures. Issue 1 (December 2020) - Sunil, S; Naga kumar, M S
Abstract: Semi rigid mixture is a unique type of mixture in recent years, which has two components:Open graded bituminous mix and cement mortar grout. In this study, engineering and strength properties of semi rigid mixtures with three selected gradations are investigated. The flowability, compressive strength and flexural strength are identified to measure the optimum cement mortar grout. Meanwhile for Open graded bituminous mix, volumetric analysis, drain down and cantabro abrasion loss tests are carried out for selected gradations by varying binder content to obtain optimum mixture. Further the compressive strength, flexural strength, stability, tensile strength and durability tests are evaluated for the selected gradations of optimised Semi Rigid mixtures. The results showed that cement mortar grout containing cement to M-Sand ratio of 1:1, water-cement ratio of 0.35 with super plasticizer (polycarboxylic ether polymer) dosage of 0.45% resulted in desired flow of 12 seconds, compressive strength and flexural strength of 27 MPa and 3.5 MPa respectively. The optimum binder contents of Open graded bituminous mix for the selected gradations are found to be in the range of 4.5-5.0%. Furthermore the obtained 4.5% binder content in Semi Rigid mixture have higher engineering and strength properties compared to 5.0% binder content .